KOMPETENSI, DISIPLIN KERJA DAN KINERJA PEGAWAI - Dody Hidayat (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Competence, Work Discipline and Employee Performance. The aim of this study was to analyze the competence and discipline significant effect on the performance of work organization Forest Management Unit (FMU) of Riau Province. This research was conducted in four (4) Organization of Forest Management Unit (FMU) of Riau Province. According to the research methods included into the survey. The method used is the census sample with a sample of 36 people. Data collection techniques using three approaches namely interviews, questionnaires and documentation so that all the necessary data can be collected quickly and systematically. Analysis of data using multiple linear regression analysis to examine the effect of independent variables inferential competence and discipline on the dependent variable of employee performance. The results showed competence and discipline significant effect on the performance of employees Organization of Forest Management Unit (FMU) of Riau Province. Competence and discipline of work together and partial positive and significant impact on employee performance Organization of Forest Management Unit (FMU) of Riau Province. It gives the sense that the better competence and discipline employees who owned the higher the employee’s performance. Competence effect is more dominant than the disciplined employee organization Forest Management Unit (FMU) of Riau Province.